Industrial attachment report on conversion of chemical odour system to biological odour system in Changi WRP - Teo, Kai Wen. (2013)
The author of the report had undergone 22 weeks of industrial attachment with Public Utilities Board, Changi Water Reclamation Plant (CWRP). She was assigned to convert chemical odour system to biological odour system using existing structure and media in CWRP. She must also assess the feasibility of the biological system under actual field conditions.